Keanekaragaman Makrozoobenthos di Sungai Logawa, Jawa Tengah - Puspitasari, Hesti; Fikriyya, Nabela; Fianjani, Ajeng Sekar; Viana, Rezza Octela; Transendenti, Aura Saintia; Handayani, Anik Maulia Tri; Adharani, Nadya (MAIYAH, 2023)
The Logawa River is one of the rivers in Banyumas Regency, Central Java Province and flows from a spring in the Windusari, Kalisalak village. The flow of the Logawa River experiences a lot of waste input from various sources, such as sand mining waste and household waste. This allows for a decrease in water quality in the Logawa River. One way to determine water quality is by using biological parameters, for example macrozoobenthos. This research was conducted to determine the quality of water in the Logawa River based on the diversity of macrozoobenthos which was analyzed using the calculation of the Shannon Wiener Diversity Index (H') and Simpson Dominance Index (C). The sample collection method in this study was a field survey which was then observed using a stereo microscope. There are three sampling stations, namely the upstream, downstream and middle stations with two sampling times. The diversity index values obtained ranged from 0.62 - 1.89. The low value of the macrozoobenthos diversity index indicates the negative impact of the sand mining activity. The data obtained were then analyzed for the relationship between existing macrozoobenthos diversity and water quality using Pearson Correlation. Water quality parameters used include temperature, current velocity, pH, Dissolved Oxygen (DO), and Chemical Oxygen Demand (COD). The water quality parameter that has the most influence on macrozoobenthos diversity in the Logawa river is COD, with a correlation coefficient of -0.79 in the 1st sampler and -0.98 in the 2nd sampler. The results of the analysis show that the Logawa River is experiencing turbidity caused by sand mining activities